Adalimumab for induction of clinical remission in moderately to severely active ulcerative colitis: results of a randomised controlled trial. Issue 6 (5th January 2011) - Reinisch, Walter; Sandborn, William J; Hommes, Daniel W; D'Haens, Geert; Hanauer, Stephen; Schreiber, Stefan; Panaccione, Remo; Fedorak, Richard N; Tighe, Mary Beth; Huang, Bidan; Kampman, Wendy; Lazar, Andreas; et al.
Abstract : Objective: The aim of this study was to assess the efficacy and safety of adalimumab (ADA), a recombinant human monoclonal antibody against tumour necrosis factor α (TNF), for the induction of clinical remission in anti-TNF naïve patients with moderately to severely active ulcerative colitis. Methods: This 8-week, multicentre, randomised, double-blind, placebo-controlled study (NCT00385736 ), conducted at 94 centres in North America and Europe, enrolled ambulatory adult patients with Mayo score of ≥6 points and endoscopic subscore of ≥2 points despite treatment with corticosteroids and/or immunosuppressants. Under the original study protocol, 186 patients were randomised (1:1) to subcutaneous treatment with ADA160/80 (160 mg at week 0, 80 mg at week 2, 40 mg at weeks 4 and 6) or placebo. Subsequently, at the request of European regulatory authorities, the protocol was amended to include a second induction group (ADA80/40: 80 mg at week 0, 40 mg at weeks 2, 4 and 6). The primary efficacy endpoint was clinical remission (Mayo score ≤2 with no individual subscore >1) at week 8, assessed in 390 patients randomised (1:1:1) to ADA160/80, ADA80/40, or placebo. Safety was assessed in all enrolled patients. Patients, study site personnel, investigators, and the sponsor were blinded to treatment assignment. Results: At week 8, 18.5% of patients in the ADA160/80 group (p=0.031 vs placebo) and 10.0% in the ADA80/40 group (p=0.833 vs placebo) were in remission, compared with 9.2% in the placebo group. Serious adverse events occurred in 7.6%, 3.8% and 4.0% of patients in the placebo, ADA80/40, and ADA160/80 groups, respectively. There were two malignancies in the placebo group, none in the ADA groups. There were no cases of tuberculosis and no deaths. Conclusions: ADA160/80 was safe and effective for induction of clinical remission in patients with moderately to severely active ulcerative colitis failing treatment with corticosteroids and/or immunosuppressants. Clinical trial: NCT00385736.